Coal Facies and Its Effects on Pore Characteristics of the Late Permian Longtan Coal, Western Guizhou, China. (16th November 2022) - Lou, Yi; Su, Yuliang; Wang, Wendong; Xia, Peng; Wang, Ke; Xiong, Wei; Yu, Yin; Shao, Linjie; Yang, Fuqin; Chen, Xiangping
Abstract : The coal facies and their effects on the coal pore characteristics of the Late Permian Longtan Formation, western Guizhou, were studied, using diverse experiments of macerals and minerals compositions, vitrinite reflectance, and pore characteristics. The results show that five coal facies exist in studied samples, and they are shallow-water covered forest peat swamp facies, moist forest peat swamp facies, dry forest peat swamp facies, low peat swamp facies, and wet land herbaceous peat swamp facies. Among them, the moist forest peat swamp facies accounts for the largest proportion, followed by the shallow-water covered forest peat swamp and dry forest peat swamp facies. The order of pore development degree is identical with the order of moist forest peat swamp facies coal > shallow-water covered forest peat swamp facies coal > dry forest peat swamp facies coal. In contrast to shallow-water covered forest peat swamp facies and dry forest peat swamp facies samples, moist forest peat swamp facies samples have higher porosity and larger pore size. Coal facies play an important role in controlling the pore structure of coal reservoir, which have more effect on pore size distribution than coal rank for the samples in this study.